2022
DOI: 10.1177/20420986221129335
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitors or angiotensin receptor blockers and cancer risk: an updated meta-analysis of observational studies

Abstract: Introduction: Debate on the association between the use of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) and the risk of developing cancer has been ongoing for decades. This study aimed to generate reliable results by analysing observational studies published in the decade after our last meta-analysis was conducted. Methods: We searched Embase and Medline databases on 21 January 2021 for cohort and case-control studies. Two researchers independently reviewed the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Lee SH et al (2022) conducted a population-based cohort study in Korea and indicated that RAAS inhibitors use was not associated with gynecologic cancers [ 44 ]. A meta-analysis of observational studies found no preventive effect of RAAS against gynecologic cancers [ 45 ]. Inconsistences between our finding and other studies may be due to the differences in study design, and adjusted confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Lee SH et al (2022) conducted a population-based cohort study in Korea and indicated that RAAS inhibitors use was not associated with gynecologic cancers [ 44 ]. A meta-analysis of observational studies found no preventive effect of RAAS against gynecologic cancers [ 45 ]. Inconsistences between our finding and other studies may be due to the differences in study design, and adjusted confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in all cancer group the overall risk was reduced [ 54 ]. Other research team, in turn, reported an increased risk of melanoma [relative risk (RR): 1.09, 95% CI: 1.00–1.19] and kidney cancer (RR: 1.50, 95% CI 1.01–2.23) in ACE-I-treated patients, but a decreased risk of oesophageal cancer (RR: 0.73, 95% CI: 0.57–0.94) [ 55 ]. Furthermore, a reduced survival from malignant diseases among hypertensive individuals emerged in two randomized controlled trials: with enalapril (OR = 1.59, 95% CI: 0.90–2.820) and benazepril (OR = 1.52, 95% CI: 0.45–5.42).…”
Section: Discussionmentioning
confidence: 99%
“…Safety concerns, in particular, relate to their pro-carcinogenic potential, evidenced by increased incidence of malignancy among ACE-Is users [3,4]. Specifically, the risk regards common neoplastic conditions such as: endometrial [5,6], melanoma, kidney and female reproductive cancers [7][8][9][10][11]. Furthermore, their capacity to stimulate lung cancer, which is the most common human neoplastic condition [12][13][14], was implied.…”
Section: Introductionmentioning
confidence: 99%